Root effect also functions modulating the hemichrome stability in tetrameric hemoglobins - VERGARA, ALESSANDRO; FRANZESE, MARISA; MERLINO, ANTONELLO; BONOMI, GIOVANNA; MAZZARELLA, LELIO; C. Verde; D. Giordano; G. Di Prisco; C. Lee; J. Peisach (country:ITA, 2008)
Oxidation of hemoglobins leads to the formation of Fe(III) forms, whose relevance spans from biochemical to physiological aspects 1. Here we report a combined EPR/X-ray crystallography study at acidic pH on six ferric tetrameric hemoglobins (Hbs), five isolated from the Antarctic fish species Trematomus bernacchii, Trematomus newnesi, and Gymnodraco acuticeps, and one from the sub-Antarctic fish Cottoperca gobio. Our data reveal that, in all the studied Hbs, aquomet form and two hemichromes coexist at acidic pH, analogously to what happens at physiological pH 2. Nevertheless, the EPR analysis reveals that, only for the three Root effect hemoglobins 3,4, a significant amount of pentacoordinated (5C) high-spin Fe(III) species appears at acidic pH. The crystal structure at acidic pH of the ferric hemoglobin from Trematomus bernacchii, endowed with Root effect 4, is also reported at 1.7 Å. Indeed, this structure reveals a 5C state both at α- and β-chains within a T-like quaternary structure. The ability of the Antarctic fish Hbs to form 5C states in various conditions prompted us to perform a peroxidase activity study. These proteins exhibit a peroxidase activity higher than that observed for mammalian and temperate fish Hbs , thus suggesting that a partial hemichrome state in tetrameric Hbs does not protect them from peroxidation as previously proposed 5. This work was financially supported by PNRA (Italian National Programme for Antarctic Research) 1 A. Vergara, L. Vitagliano, G. di Prisco, C. Verde, and L. Mazzarella, Meth. Enz. 436A, 421 (2008). 2 A. Vergara, M. Franzese, A. Merlino, L. Vitagliano, G. di Prisco, C. Verde, H. C. Lee, J. Peisach, and L. Mazzarella, Biophys. J. 93, 2822 (2007). 3 L. Mazzarella, G. Bonomi, M. C. Lubrano, A. Merlino, A. Vergara, L. Vitagliano, C. Verde, and G. di Prisco, Proteins: Struct. Funct. Bioinf. 62, 316 (2006). 4 L. Mazzarella, A. Vergara, L. Vitagliano, A. Merlino, G. Bonomi, S. Scala, C. Verde, and G. di Prisco, Proteins: Struct. Funct. Bioinf. 65, 490 (2006). 5 L. Feng, ...